Technology-related safety strategies among college student survivors using campus-based advocacy services - PettyJohn, Morgan E. (Violence and victims, 2025)
Technology can be leveraged as a tool by perpetrators of interpersonal violence, which requires survivors to consider digital platforms as part of their safety planning processes. To explore how survivors are addressing these safety concerns, we performed secondary, qualitative content analysis of semistructured interviews with college students who used campus-based advocacy services for interpersonal violence. Participants described an array of technology-related safety strategies they implemented to protect themselves across multiple types of digital technologies. As a cohort of the internet age, many college student survivors reported having an extensive "digital footprint" which created challenges in identifying and addressing all possible security concerns. Campus-based advocacy services should integrate technology considerations into their safety planning using a survivor-led, empowerment approach which helps maintain access to digital platforms.